2015
DOI: 10.1016/j.pec.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Educational interventions for cancer pain. A systematic review of systematic reviews with nested narrative review of randomized controlled trials

Abstract: Suggestions are made to aid the development of future interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 67 publications
3
83
0
5
Order By: Relevance
“…The underpinning theory is that attitudes and beliefs inform behaviour and lead to poor adherence to medication regimens that in turn give rise to sub-optimal pain relief. While this theory has informed research on educational interventions to tackle sub-optimal pain management practices, a recent review of reviews concluded that although such interventions can have a very small impact on pain intensity, their clinical significance is questionable 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The underpinning theory is that attitudes and beliefs inform behaviour and lead to poor adherence to medication regimens that in turn give rise to sub-optimal pain relief. While this theory has informed research on educational interventions to tackle sub-optimal pain management practices, a recent review of reviews concluded that although such interventions can have a very small impact on pain intensity, their clinical significance is questionable 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer pain control is frequently suboptimal, despite effective treatments being available 2. Under-reporting of pain by patients, inadequate communication about pain between patients and healthcare professionals, and inadequate assessment of pain by professionals are known to contribute to poor pain control 3 4…”
Section: Introductionmentioning
confidence: 99%
“…Interventions which target these processes may improve symptom management in CrF [37]. In our intervention, the aim was to help the participant engage in a process of appraising their representation of the fatigue symptoms, and also help them to identify adaptive coping strategies hypothesized to mediate change in fatigue outcomes [14,33].…”
Section: Methodsmentioning
confidence: 99%